Crack simulation and probability analysis using irregular truss structure modeling equivalent to a continuum structure - Choi, Won; Yoon, Seongsoo; Lee, JeongJae (International Journal of Agricultural and Biological Engineering, 2017)
The problems related to agricultural structure engineering for crack simulation and reliability analysis are complicated because its variables contain wide ranges of mean and standard deviation. This paper describes an integrated model to perform crack simulation and reliability analysis of a continuum structure. The structure is assumed to be under a two-dimensional plane stress and the deformation is infinitesimal. A truss structure model that has the same behaviour as a continuum structure was developed using irregular triangle truss components where each element consists of two hinges with an axial degree of freedom at both of their ends. A Monte-Carlo simulation (MCS) was adopted for the reliability analysis. If the length of one side of the irregular triangle mesh is shorter than the thickness of the structure, the slenderness associated with compressive failure needs to be examined only for the short column. For that reason, the failure criterion suitable for the equivalent truss structure model was established by checking only axial stresses acting on truss members. Since nodes of the equivalent truss structure model for the structural analysis in this study consist of hinges, development of plastic hinges that occurred during crack propagation were not considered in this model. To simulate the development of crack, truss members over allowable stresses of tension or compression among truss members with the largest amount of stress at each completed structural analysis time step were sequentially removed. Since irregular triangle meshes have an uncertainty in themselves to compare with regular meshes, the equivalent truss structure model could describe crack propagation more realistically. The failure probabilities of structures under various loads and boundary conditions had good agreement with the analytical solutions directly solved from the limit state equations expressed in the form of moments. Keywords: crack simulation, probability analysis, irregular truss structure model, failure criteria, Monte Carlo simulation DOI: 10.3965/j.ijabe.20171001.2024 Citation: Choi W, Yoon S, Lee J. Crack simulation and probability analysis using irregular truss structure modeling equivalent to a continuum structure. Int J Agric & Biol Eng, 2017; 10(1): 234–247.